2018
DOI: 10.3390/min8040139
|View full text |Cite
|
Sign up to set email alerts
|

Shock-Induced Olivine-Ringwoodite Transformation in the Shock Vein of Chondrite GRV053584

Abstract: Shock metamorphism of minerals in meteorites could help to understand the shock history of its parent body and also provide a window into the interior of the Earth. Although shock features in olivine have been well known within and adjacent to shock melt veins and shock melt pockets in meteorites, there are processes that are not yet completely understood. Ringwoodite is formed by crystallization from olivine melts or solid-state phase transformation of olivine. Typically, olivine clasts with a ringwoodite rim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In ordinary chondrites, wadsleyite and ringwoodite aggregates have been typically found within and/or in the surrounding of the shock features (Chen et al 2004;Yin et al 2018;Miyahara et al 2020), and ringwoodite has been also found in association with ferropericlase (Chen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In ordinary chondrites, wadsleyite and ringwoodite aggregates have been typically found within and/or in the surrounding of the shock features (Chen et al 2004;Yin et al 2018;Miyahara et al 2020), and ringwoodite has been also found in association with ferropericlase (Chen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of chemical compositions, some ringwoodite lamellae and polycrystalline grains have almost identical compositions to the original olivine, indicating an interface-controlled growth process (Xie and Sharp 2007;Mosenfelder et al 2001;Ohtani et al 2004;Chen et al 1996) in which the growth of ringwoodite is controlled by the rate of short range diffusion across the interface between the two phases (Sharp and De Carli 2006). Some polycrystalline ringwoodite rims surrounding the olivine show a Fe-Mg diffusion-controlled growth process (Walton and McCarthy 2017;Yin et al 2018;Pittarello et al 2015) with Fe preferentially partitioned to ringwoodite, leading to a higher FeO content of ringwoodite compared with the residual olivine.…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature and high pressure induced by an impact event can cause special deformation features in rocks and minerals, known as shock metamorphism [3]. Shock features of feldspar have been observed in impactites from impact craters on Earth [4,5], ordinary chondrites [6,7], as well as Vesta [8], Lunar [9] and Martian [10] meteorites. The currently known shock-metamorphic features in natural feldspar include irregular fractures and planar fractures [5], undulatory extinction and mosaicism [11], planar deformation features (PDFs) [12], diaplectic glass (sometimes called maskelynite) [4,13], vesicular glass [14], lingunite [15], and decomposition [16].…”
Section: Introductionmentioning
confidence: 99%